STRATEGI PENGEMBANGAN USAHA PADA TOKO NUGIN DI KECAMATAN REMBON KABUPATEN TANA TORAJA - Marsal Samaya; Lisa K. Wibisono; Helba Rundupadang (JURNAL ILMIAH EDUNOMIKA, 2025)
MARSAL SAMAYA, 2025 Business Development Strategy at Nugin Store, Rembon District, Tana Toraja. This study aims to determine the business development strategies at Toko Nugin in Rembon District, Tana Toraja Regency. The research method used is a descriptive qualitative approach and SWOT analysis. The data used in this study includes primary and secondary data, with data collection techniques involving observation, interviews, and library studies. The data obtained from the data collection is then analyzed using SWOT analysis to identify the strengths, weaknesses, opportunities, and threats for Toko Nugin in Rembon District. Based on the research findings, the IFAS matrix obtained a total score for strengths and weaknesses of 3.6, as the total score above 2.93 indicates that the internal position of the company is quite strong. The EFAS matrix obtained a total score for opportunities and threats of 3.17, as the total score approaching 4.0 indicates that Nugin Store responds to existing opportunities in an exceptional way and avoids threats in the market. The SWOT matrix results show that the business development strategy is to maintain product quality, sustain service quality to customers, uphold customer trust, add employees at Nugin Store, expand the space or building at Nugin Store, increase the variety of agricultural commodity products, create price promotions or discounts to attract consumers to purchase those goods, enhance marketing strategies through social media by keeping up with technological advancements, and improve the service system so that consumers feel comfortable shopping. Keywords: Development Strategy, SWOT Matrix, IFAS, and EFAS